Application of transpiration cooling on hypersonic vehicles to mitigate material oxidation - Ewenz Rocher, M (2021)
This thesis investigates the application of transpiration cooling to mitigate material oxidation of hypersonic vehicles. This was motivated by the early onset of surface oxidation of many high-temperature aerospace materials and the resulting limitation of the flight envelope. For example, Ultra-High-Temperature Ceramics have melting points exceeding 3500 K, thus could balance the incoming heat flux through re-radiation alone, but start oxidising at 1000 K, which limits the passive cooling capability severely. The aim of this thesis is to increase this oxidation limit by shielding the surface from freestream oxygen through boundary layer mass injection.